1998
DOI: 10.1080/010503998422629
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Disturbances Caused by Long-term Exposure to Industrial Solvents. Relation to the Diagnosis of Toxic Encephalopathy

Abstract: Sixty workers, consecutively admitted due to suspicion of solvent-induced chronic toxic encephalopathy (CTE), were investigated with pure-tone audiometry, determination of speech recognition of monosyllabic words and distorted speech and cortical response audiometry (CRA). Eighteen workers not exposed to occupational solvents and noise were also investigated. The scores in the distorted speech test were significantly lower and the CRA latencies were significantly longer in the solvent group than in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 7 publications
1
21
0
4
Order By: Relevance
“…[168][169][170][171][172][173] This suggests that hearing loss caused by chemicals can affect a worker's life more extensively than noise-induced hearing loss, because sounds are perceived not only as less loud, but also as distorted. Word recognition may also be compromised.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…[168][169][170][171][172][173] This suggests that hearing loss caused by chemicals can affect a worker's life more extensively than noise-induced hearing loss, because sounds are perceived not only as less loud, but also as distorted. Word recognition may also be compromised.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…For example, impaired speech recognition scores consistent with a retrocochlear pattern and/or abnormal cortical responses and/or abnormal reflex decay have been reported in populations working with toluene, 5 jet fuels, 8 styrene 9 and mixtures of solvents. 8,10 -12 It is now documented that solvents should be considered as individual substances with different specific toxicities, 12 and that solvents may act on transmitters specific for certain neural structures and pathways. 10 For example, significantly delayed auditory brainstem responses (ABRs) were measured in a group of normally hearing workers professionally exposed to toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found dysfunction of the central auditory nervous system (CANS) in workers exposed to a mixture of solvents (Fuente et al, 2006;Fuente & McPherson, 2007;Laukli and Hansen, 1995;Moen et al, 1999;Niklasson et al, 1998;Ödkvist et al, 1987;Ödkvist et al,1992;Pollastrini et al, 1994;Varney et al, 1998). Fuente et al (2006), Fuente & McPherson (2007), and Fuente (2008) have shown that workers exposed to a mixture of solvents (toluene, xylene and methyl ethyl ketone) may acquire central auditory dysfunction as evidenced by abnormal results for a set of behavioural central auditory processing tests.…”
Section: Evidence Of the Adverse Effects Of Solvents On The Central Amentioning
confidence: 99%